Training and Development and turnover intentions among staff of colleges of education in Bono and Ahafo regions of Ghana - Yeboah, Stella Asraa (University of Cape Coast, 2023)
The main purpose of the study was to examine the effect of employee training and development on employee turnover intentions among staff of Colleges of Education in Bono and Ahafo Regions of Ghana. In order to achieve the purpose of the study, three specific objectives were stated. They were; to analyse the effect of on-the-job training on employee turnover intention among staff of the College of Education in Bono and Ahafo Regions of Ghana; to examine the effect of off-the-job training on employee turnover intention among staff of the Colleges of Education in Bono and Ahafo Regions of Ghana.; to analyse the effect of employee development on employee turnover intention among staff of the Colleges of Education in Bono and Ahafo Regions of Ghana. The study was centered on resource-based view theory and social capital theory. With respect to the study’s methodology, the quantitative approach was used. The explanatory research design was employed since the research studied on the causal relationship between training and development and employee turnover intentions. The data collection instrument was questionnaire. The simple random sampling technique was used in selecting respondents of 385. Descriptive and structural equation model were also used to analyse the objectives of the study. The study found that, on-the-job training, off-the-job training and employee development had a significant effect on employees. The study recommended that management must provide regular opportunities for staff to engage in professional development and training.
x,116p:,ill
Keywords: Education; employee training and development